Variability of morphometrical characteristics of needles at a clonal plantation of plus trees of scots pine (Pinus sylvestris L.) - N. N. Besschetnova; V. P. Besschetnov (Вавиловский журнал генетики и селекции)
The formation of plus trees assortment for seed orchards is one of the most difficult problems of contemporary forest breeding. This problem is related to the risk of inbreeding depression of the seed progeny of plus trees, which do not have any defense mechanism against self-pollination. Economically, the Scots pine is one of the most important wood species. Diverse characteristics of its needles make a subject for multidisciplinary research. Needle size is accepted as an indirect indicator of growth pine energy. Our research was focused on selection valuation of Scots pine plus trees by morphometric features of needles. Plus trees are represented by their clones in first-order seed orchards in the Nizhny Novgorod region. When collecting the source material, the elimination of differentiating effects of environmental factors and time factors was ensured. The dissimilarity of plus trees at a wide range of signs was manifested to different degrees. Because the heterogeneity of the assortment composition of the seed orchard in question was formed against the background of the aligned environmental conditions, there was every reason to consider it as being caused largely by hereditary factors. It was confirmed by the results of ANOVA. The predominant influence of distinctions between ortets was established. The influence of distinctions between the ramets was revealed – that was comparable to the residual variance. Pronounced heterogeneity of the composition and its genetic determinism set up conditions for effective multivariate comparisons of plus trees. Factor analysis formed its integrated independent variables from a common set of morphological parameters of needles. They are used in cluster analysis along with the original signs. Cluster analysis revealed in the seed orchards plus trees that are to the greatest extent different from the others. They can be combined with all the other plus trees in cross-breeding schemes to achieve the heterosis effect and to eliminate the risk of inbreeding depression.